Educational Equality and International Students - Hou, Minghui (Journal of International Students, 2019)
Educational Equality and International Students, recently published by Tannock (2018), explores and highlights how to conceptualize and promote principles of educational equality for both international and domestic students in the United Kingdom. Tannock’s book includes empirical research consisting of 60 interviews with higher education staff and students, as well as the use of higher education institutional documents and secondary statistics collected from universities and national higher education organizations around the UK. Tannock addresses the contradictions between the missions of higher education institutions (universalistic principles of human rights in equal education) and their practices regarding international students as “cash cows” that keep the university afloat (p. 110).